2003
DOI: 10.1096/fj.02-0939com
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin‐regulated recruitment of vascular smooth muscle cells by endothelial‐derived heparin binding EGF‐like growth factor

Abstract: Recruitment of vascular smooth muscle cells (SMC) by endothelial cells (EC) is essential for angiogenesis. Endothelial-derived heparin binding EGF-like growth factor (HB-EGF) was shown to mediate this process by signaling via ErbB1 and ErbB2 receptors in SMCs. 1) Analysis of ErbB-ligands demonstrated that primary ECs expressed only HB-EGF and neuregulin-1. 2) Primary SMCs expressed ErbB1 and ErbB2, but not ErbB3 or ErbB4. 3) Consistent with their known receptor specificities, recombinant HB-EGF, but not neureg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 49 publications
(71 reference statements)
4
92
0
1
Order By: Relevance
“…The inhibition of vSMC recruitment is not complete in our pdgrfrbDN experiments. This raises the possibility that other mechanisms besides PDGF signaling may also be used to help vSMC 'home' to vessels (Lee et al, 2007;Higashiyama et al, 1993;Iivanainen et al, 2003;Krymskaya et al, 1997;Wang et al, 2014Wang et al, , 2012Kofler et al, 2015;Fortuna et al, 2015;Kennard et al, 2008;Hirschi et al, 2003;Aplin et al, 2010;Stratman et al, 2010;Zaucker et al, 2013). However, it is also possible that we are simply not able to sufficiently eliminate vSMC PDGF signaling using this method and that residual vSMC recruitment reflects this 'bleed through'.…”
Section: Ontogeny Of Vsmcs Associated With the Zebrafish Dorsal Aortamentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of vSMC recruitment is not complete in our pdgrfrbDN experiments. This raises the possibility that other mechanisms besides PDGF signaling may also be used to help vSMC 'home' to vessels (Lee et al, 2007;Higashiyama et al, 1993;Iivanainen et al, 2003;Krymskaya et al, 1997;Wang et al, 2014Wang et al, , 2012Kofler et al, 2015;Fortuna et al, 2015;Kennard et al, 2008;Hirschi et al, 2003;Aplin et al, 2010;Stratman et al, 2010;Zaucker et al, 2013). However, it is also possible that we are simply not able to sufficiently eliminate vSMC PDGF signaling using this method and that residual vSMC recruitment reflects this 'bleed through'.…”
Section: Ontogeny Of Vsmcs Associated With the Zebrafish Dorsal Aortamentioning
confidence: 99%
“…Pericytes associate with these smaller-caliber vessels in lower numbers, with pericyte/EC ratios between 1:1 and 1:10, localizing primarily along endothelial cell-cell junctions, branch points, and in areas that need to maintain high levels of barrier function [such as the blood-brain barrier (BBB)] (Ando et al, 2016;Owens, 1995;Daneman et al, 2010;Armulik et al, 2010Armulik et al, , 2011a. PDGF-BB/PDGFRβ signaling is required for recruitment of vSMCs and pericytes to vessels (Hellstrom et al, 1999;Fortuna et al, 2015;Lindblom et al, 2003;Lindahl et al, 1997;Hirschi et al, 1999;Lehti et al, 2005;Benjamin et al, 1998), although a variety of other signaling pathways have been shown to contribute to mural cell differentiation, recruitment and stabilization, in particular TGFβ, Notch and EGF signaling among others (Lee et al, 2007;Higashiyama et al, 1993;Iivanainen et al, 2003;Krymskaya et al, 1997;Wang et al, 2014Wang et al, , 2012Kofler et al, 2015;Fortuna et al, 2015;Kennard et al, 2008;Hirschi et al, 2003;Aplin et al, 2010;Stratman et al, 2010;Zaucker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Tie2 is activated in the endothelium of quiescent adult vasculature, and is believed to be involved in the maintenance of vascular quiescence (6,32). Furthermore, both Ang1/Tie2 and Dll4/ Notch signaling promote recruitment of mural cells to the vessel wall and induce deposition of basement membrane proteins around the vessels, both of which are important for vascular stabilization (26,(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…In contrast, tumor endothelial cells acquire the EGFR and down regulate ErbB3 expression both in vitro and in vivo. Endothelial cells in culture also express EGFR and ErbB4 ligands HB-EGF and NRG-1 (124)(125)(126). It is thought that HB-EGF signaling through both the EGFR and Erbb4 helps recruit pericytes to capillaries to stabilize the structures (125).…”
Section: Ereg and Lung Metastasesmentioning
confidence: 99%
“…Endothelial cells in culture also express EGFR and ErbB4 ligands HB-EGF and NRG-1 (124)(125)(126). It is thought that HB-EGF signaling through both the EGFR and Erbb4 helps recruit pericytes to capillaries to stabilize the structures (125). The addition of exogenous EGF to tumor endothelial cells in vitro increases their proliferation (124).…”
Section: Ereg and Lung Metastasesmentioning
confidence: 99%